Nature Benefits in Kenya: an Atlas of Ecosystem and Human Well-Being - Said, Mohammed Yahya; Okwi, P.; Ndeng'e, G.; Agatsiva, J.; Kilele, X. (World Resources Institute, 2007)
Nature’s Benefits in Kenya: An Atlas of Ecosystems and Human Well-Being integrates spatial data on poverty and the environment in Kenya, providing a new approach to examining the links between ecosystem services (the benefits derived from nature) and the poor. This publication focuses on the environmental resources most Kenyans rely on to earn their livelihoods, such as soil, water, forest, rangeland, livestock, and wildlife. The atlas overlays georeferenced statistical information on population and household expenditures with spatial data on ecosystems and their services (water availability, wood supply, wildlife populations, and the like) to yield a picture of how land, people, and prosperity are related in Kenya. In Kenya’s national development plans, improving the health and prosperity of Kenyan families while also safeguarding the natural environment and the many important economic and spiritual benefits it provides are identified as top priorities. Attaining these multiple development goals means that policymakers and civil society groups need to access information and analysis on the numerous interconnections among environmental resources, human well-being, and economic expansion. The maps and analyses presented in this atlas are a first attempt to provide such information. This information can be used in developing poverty reduction programs and in designing policies for water resources management, agriculture production, biodiversity preservation, and charcoal production, among others. The maps and analyses presented here will not provide easy answers to questions concerning the causes of poverty in Kenya and how ecosystems can best be managed to increase economic growth and improve livelihoods. But they are a first step toward stimulating more informed dialogue and provoking questions for which answers may be found. With up-to-date data and additional analyses, the implementation of Kenya’s Economic Recovery Strategy (and its successor strategy) can be targeted to specific geographic areas of the country, focusing on the poor, and making better use of Kenya’s natural resources.